(untitled) (REMUNOM, 2023)
The social assistance policy promises social transformation, through the emancipation of the individual, but in practice what you see is a feeling of skating on ice. Therefore, the objective of this work was to understand how psychologists are intervening in Basic Social Protection, in order to identify how professionals are working to achieve social transformation. It was possible to observe that in practice there is a reduction of social issues only in the family, blaming it for all social problems. Furthermore, without a critical understanding of reality and making users dependent on the service/technician, what is seen is a social control that aims to maintain the capitalist status quo.